Analisis Minat Belajar Siswa Kelas 3 SDN 2 Bendungan Dalam Pembelajaran Tematik Dengan Model TPS (Think Pair Share) Berbasis STEM (Science, Technology, Engineering, Mathematic) - Riza Rahma Diana; Eka Yuliana Sari (Pendagogia: Jurnal Pendidikan Dasar, 2024)
This study aims to analyze and describe the learning interests of grade 3 students of SD Negeri 2 Bendungan in thematic learning with a STEM -based TPS (Think Pair Share) model (Science, Technology, Engineering, And Mathematics). This type of research is descriptive qualitative with observation research instruments, questionnaires, and interviews. The results of this study are the average percentage of students who are classified as very high with a score of 81%-100% and students who are classified as high in the high category with a score of 61%-80%, namely students who respond according to aspects of learning interest. The average percentage of students who are classified as moderate with a score of 41%-60% and students who are classified as low in the category with a score of 21%-40% are students who do not respond according to aspects of learning interests. The conclusion of the study is that 75% of 100% of students indicated having an interest in learning and the rest was 25%. Therefore, the STEM -based TPS (Think Pair Share) learning model (Science, Technology, Engineering, And Mathematics) in thematic learning can really increase the interest in learning grade 3 students of SD Negeri 2 Bendungan.